2002
DOI: 10.1097/00008480-200212000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and ethical issues in the conduct of clinical research involving children

Abstract: Children are a uniquely vulnerable population, yet there is an overwhelming need to test safety and efficacy of therapies and preventions in the pediatric population. Results from studies in adults do not provide sufficient or accurate information. Recently, the need for research involving children has been recognized and action has been taken at the federal level to address both the need for pediatric research and the protection of the welfare and rights of children as research subjects. Other ethical and leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Neuropsychological AED data in children are limited 22 and adult AED findings are not readily generalizable to children. 23 For example, the primary behavioral phenobarbital side effect is hyperactivity in children, depression in young adults, and sundowning in the elderly. Although neuropsychological impairment may be present at the time of initial diagnosis, 24 AED exposure during neurodevelopment can produce impairments that may continue into adulthood even after AED discontinuation.…”
Section: Fetal Aed Risks For Autism and Autisticmentioning
confidence: 99%
“…Neuropsychological AED data in children are limited 22 and adult AED findings are not readily generalizable to children. 23 For example, the primary behavioral phenobarbital side effect is hyperactivity in children, depression in young adults, and sundowning in the elderly. Although neuropsychological impairment may be present at the time of initial diagnosis, 24 AED exposure during neurodevelopment can produce impairments that may continue into adulthood even after AED discontinuation.…”
Section: Fetal Aed Risks For Autism and Autisticmentioning
confidence: 99%
“…Although Moser et al [ 30 ] demonstrated a correlation between salsolinol levels in urine and CSF and a time course study of N-methyl-norsalsolinol in CSF indicated a parallel decline of TIQ derivatives on both sides of the blood-brain barrier [ 17 , 31 ] the evidence for a reliable correlation between TIQ levels in urine and the central nervous system remains limited. However, analyses of urine levels seem to be methodologically and ethically justified as the first step to investigate TIQ in children with ADHD, because in studies analyzing other dopamine metabolites in the CSF, the lack of a control group [ 9 ] due to ethical considerations [ 32 ] limited the significance of the findings and they were not superior to the results of plasma or urine analyses. Nevertheless, increased central dopamine concentrations might cause increased concentrations of salsolinol and norsalsolinol in urine resulting also in increased urine concentrations of N-methyl-salsolinol and N-methyl-norsalsolinol.…”
Section: Discussionmentioning
confidence: 99%
“…5 It can be argued that fertility preservation aimed at children is ethical because it prevents morbidity (reproductive and psychosocial) and it safeguards their reproductive autonomy. 6 Therefore, the main ethical question concerns the process involved in achieving fertility preservation and the techniques that are required.…”
Section: Ethics Of Fertility Preservation In Cancer Patients 719mentioning
confidence: 99%
“…As a result, they require special protection against potential violation of their rights that may occur during research investigations. 4,5 Until very recently, institutional attitudes impeded significant participation by children in medical research for fear of exploitation.…”
Section: Ethics Of Fertility Preservation In Cancer Patients 719mentioning
confidence: 99%
See 1 more Smart Citation